2015
DOI: 10.21149/spm.v57i5.7625
|View full text |Cite
|
Sign up to set email alerts
|

Salud global 2035: un mundo convergiendo en el lapso de una generación

Abstract: Con motivo del 20º aniversario del Informe sobre el Desarrollo Mundial 1993, una Comisión de la revista The Lancet reconsideró el argumento a favor de la inversión en salud y desarrolló un nuevo marco de inversión para lograr mejoras dramáticas en materia de salud para el año 2035. El informe de la Comisión contiene cuatro mensajes clave, cada uno acompañado de oportunidades para los gobiernos nacionales de países de ingresos bajos y medios y para la comunidad internacional. En primer lugar, invertir en salud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(31 reference statements)
1
6
0
1
Order By: Relevance
“…In this study, we used both standard and inequality based convergence metrics to test the hypothesis of convergence both in averages and relative distribution of LEB and IMR in 193 countries worldwide. Our results confirm the findings of previous studies [ 1 , 12 , 14 , 15 , 16 , 18 , 20 ] that found evidence of considerable progress in global averages of LEB and IMR. Our findings revealed a trend of ‘rise-fall-rise’ in inequalities in world health status during the period 1950 to 2015, despite the fact that the speed of fall being slow in the recent times.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we used both standard and inequality based convergence metrics to test the hypothesis of convergence both in averages and relative distribution of LEB and IMR in 193 countries worldwide. Our results confirm the findings of previous studies [ 1 , 12 , 14 , 15 , 16 , 18 , 20 ] that found evidence of considerable progress in global averages of LEB and IMR. Our findings revealed a trend of ‘rise-fall-rise’ in inequalities in world health status during the period 1950 to 2015, despite the fact that the speed of fall being slow in the recent times.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study in the context of existing literature in the field suggests that a significant amount of this divergent progress is possibly coming from within country socio-economic and regional inequalities among laggard countries which adversely affects their overall progress [ 1 , 21 , 30 ]. With economic growth, not everyone is getting rich at the same time, and not everyone is getting immediate access to the latest life-saving measures due to pre-existing social hierarchies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Un alto nivel de salud contribuye al crecimiento económico y de los ingresos y a disminuir los entornos de desigualdad entre países [18][19][20][21], más aún en América Latina que se caracteriza por ser la región con mayor inequidad en cuanto al acceso a servicios de salud [2] generando un GBS mayor en varios países [4,6,8,9,22]; en la figura N°1 se puede observar los GBS y el gasto público en salud per-cápita para el periodo 2010-2015 [23].…”
Section: Introductionunclassified